Shear failure behavior of CFRP/Al and steel/Al electromagnetic self-piercing riveted joints subject to high-speed loading. (15th December 2019) - Jiang, Hao; Sun, Liqiang; Liang, Jusong; Li, Guangyao; Cui, Junjia
Abstract: In this paper, the electromagnetic self-piercing riveted (E-SPR) technique was employed to rivet carbon fiber reinforced plastics and aluminum (C-A), as well as high strength steel and aluminum (S-A). The shear failure behaviors of the riveted joints under different loading speeds were investigated and compared. The shear experiments and full-field strain measurements were carried out. The test results showed that the shear strength of S-A joints was higher than that of C-A joints. Besides, for both joints, the maximum shear load at higher tensile speeds was larger than that at lower tensile speeds. The energy absorption of both C-A and S-A joints decreased with the increase of the loading speed. Full-field strain analysis showed that loading rate and material combination had a significant influence on joint failure behavior. For C-A joint, CFRP sheet around the rivet damaged and Al sheet bent at all tensile speeds. For S-A joint, the steel sheet bent to varying degrees at different tensile speeds. Local deformation and large area bending occurred on the Al sheet at quasi-static and high speed tensile processes, respectively. Finally, based on above results and analysis, the shear failure mechanism was discussed.